Sociolectic Variations in Alternative Universe (Au) Stories in Application X - Asil Rahmatika; Yunidar; Moh. Tahir (Universitas Islam Negeri Palopo, 2026)
This study aims to describe the forms of sociolectic variation and the factors that influence the emergence of sociolectic variation in the story of the Alternative Universe (AU) on application X. The rapid development of the Alternative Universe (AU) as a form of digital literature makes it a space that represents the language practice of the younger generation on social media. Although sociolinguistic studies on language in digital media have been widely conducted, research that specifically examines sociolinguistic variation in AU stories as digital literary products is still relatively limited. Therefore, this study seeks to fill the gap in the study by focusing on the analysis on the form of sociolectic variation and the social factors that influence the emergence of sociolectic variation in the AU story. This research is descriptive qualitative research with a sociolinguistic approach. Data in the form of words and phrases containing sociolectic variations were collected through reading, note-taking, and documentation techniques. Data analysis was carried out through the stages of data reduction, data presentation, conclusion drawn, and coding based on sociolectic categories according to Chaer and Agustina's theory. The results of the study showed 31 data covering eight forms of sociolectic variation, namely acrolect, basilect, slang, vulgar, colloquial, jargon, argot, and ken. The most dominant form is slang because it reflects the informal and expressive communication style that is typical among generation z in the digital space. In addition, five factors were found that affect the emergence of sociolinguistic variations in AU stories, namely gender, interlocutor and speech situation, occupation, social environment and cultural, and age. These findings show that language variations in AU stories not only serve as a means of communication, but also as a representation of social identity, relationships between characters, and digital communication culture of the younger generation. Theoretically, this research requires a sociolinguistic study in the realm of digital literature, while practically providing an understanding of the dynamics of language use in the contemporary digital community.